2006
DOI: 10.1002/art.21569
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to chloroquine in human CEM T cells is mediated by multidrug resistance–associated protein 1 and provokes high levels of cross‐resistance to glucocorticoids

Abstract: Objective. To explore the onset and molecular mechanism of resistance to the antimalarial diseasemodifying antirheumatic drug (DMARD) chloroquine (CQ) in human CEM T cells.Methods. Human CEM cells were used as an in vitro model system to study the development of CQ resistance by growing cells in stepwise increasing concentrations of CQ.Results. Over a period of 6 months, CEM cell lines developed 4-5-fold resistance to CQ. CQ resistance was associated with the specific overexpression of multidrug resistance-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Human monocytic-macrophage THP1 cells with various levels of acquired resistance to BTZ were selected as described previously (Oerlemans et al, 2008). Multiple human cell lines were selected based on their known expression of ABC transporters, Pglycoprotein/MDR1 (CEM/VLB) (Zamora et al, 1988), multidrug resistance-associated protein 1 (CEM/CHQ, 2008/MRP1) (Scheffer et al, 2000;Oerlemans et al, 2006), MRP2 (2008/MRP2) (Scheffer et al, 2000), MRP3 (2008/MRP3) (Scheffer et al, 2000), MRP4 (HEK293/MRP4) (Wielinga et al, 2002), MRP5 (HEK293/MRP5) (Wielinga et al, 2002), and breast cancer resistance protein (BCRP) (CEM/SSZ and MCF7/MR) (Taylor et al, 1991;van der Heijden et al, 2004). Cell cultures were maintained in RPMI 1640 medium supplemented with 10% fetal calf serum, 2 mM L-glutamine, and 1000 U/ml penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human monocytic-macrophage THP1 cells with various levels of acquired resistance to BTZ were selected as described previously (Oerlemans et al, 2008). Multiple human cell lines were selected based on their known expression of ABC transporters, Pglycoprotein/MDR1 (CEM/VLB) (Zamora et al, 1988), multidrug resistance-associated protein 1 (CEM/CHQ, 2008/MRP1) (Scheffer et al, 2000;Oerlemans et al, 2006), MRP2 (2008/MRP2) (Scheffer et al, 2000), MRP3 (2008/MRP3) (Scheffer et al, 2000), MRP4 (HEK293/MRP4) (Wielinga et al, 2002), MRP5 (HEK293/MRP5) (Wielinga et al, 2002), and breast cancer resistance protein (BCRP) (CEM/SSZ and MCF7/MR) (Taylor et al, 1991;van der Heijden et al, 2004). Cell cultures were maintained in RPMI 1640 medium supplemented with 10% fetal calf serum, 2 mM L-glutamine, and 1000 U/ml penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The growth inhibitory effects of BTZ, carfilzomib, ONX-0912, and ONX-0914 were analyzed essentially as described previously (Shafran et al, 2005;Oerlemans et al, 2006). In brief, for suspension cell cultures, 1.25 ϫ 10 5 cells/ml were plated in individual wells of a 24-well cell culture plates containing an increasing concentration of each proteasome inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…From oncology research, it has been established that specific cell membrane-associated drug efflux transporters belonging to the family of ATP-binding cassette (ABC) proteins, notably P-glycoprotein (ABCB1), multidrug resistance-associated protein 1 (MRP-1) through MRP-5 (ABCC1 through ABCC5), and breast cancer resistance protein (BCRP; ABCG2), can be induced upon therapy with various anticancer drugs to confer a phenomenon known as acquired (multi)drug resistance (6)(7)(8)(9). Studies conducted in our laboratory have shown that acquired resistance to the DMARDs sulfasalazine and chloroquine could be mediated by the increased expression of the ABC transporters BCRP and MRP-1, respectively (10)(11)(12). Furthermore, it was very recently demonstrated that LEF is a high-affinity substrate for BCRP (13).…”
mentioning
confidence: 99%
“…MTX and the antimalarial agent chloroquine are among the DMARD substrates of MRP-1, and expression of this transporter may thus confer resistance to these drugs (6,12,44). However, since MRP-1 levels in synovial T cells are rather moderate, a major contribution to a reduced response to MTX or antimalarial drugs remains elusive.…”
mentioning
confidence: 99%
“…MRP1 (ABCC1) transports both chloroquine and mefloquine (23,38). P-glycoprotein (MDR1, ABCB1) interacts with mefloquine (3).…”
mentioning
confidence: 99%